Future-Ready or Future-Blind? Activating Futures Literacy Labs of Speculative Design Methods in Higher Education - Christensen, Jeppe Kiel; Ramsgaard, Michael Breum (Tidsskrift for Social Innovation & Transformativ Entreprenørskabsdidaktik (SITE), 2026)
Exploring how quality education can be reimagined to support the institutional, human, digital, and pedagogical aspects of learning in the coming decades.